Assessing the impact of drum drying on the nutritional properties of pineapple pomace-fortified crispy mushroom sheets - Suthiluk, Phunsiri; Naradisorn, Matchima; Setha, Sutthiwal (Frontiers in Sustainable Food Systems, 2023)
The processing of ‘Phulae’ pineapple fruit for juice generates a significant by-product called pineapple pomace (PAP) that has attracted interest from the functional snack industry. Pineapple pomace (PAP) is rich source of dietary fiber and antioxidants, which make it suitable for incorporating into mushroom products that are rich in high protein content. To investigate the impact of drum drying parameters on the physicochemical properties of PAP, response surface methodology (RSM) was employed for optimization of processing parameters such as steaming temperature (130 to 170°C) and rotation speed (1 to 3 rpm). The aim was to determine the optimal conditions for achieving the highest yield of diphenylpicrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and soluble dietary fiber (SDF), which are important indicators of antioxidant activity and dietary fiber content. These optimal conditions would be used in the production of crispy Pleurotus sajor-caju (PS-PAP) and Lentinus squarrosulus (LS-PAP) sheets both of which were supplemented with PAP. The response of PS-PAP and LS-PAP to the independent variables (steaming temperature and rotation speed) was adequately described by a second-order polynomial equation. The equations demonstrated a high degree of fit with respect to DPPH (R2 = 0.9693 for PS-PAP sheet and R2 = 0.9966 for LS-PAP sheet), FRAP (R2 = 0.9908 for PS-PAP sheet and R2 = 0.9877 for LS-PAP sheet), and SDF (R2 = 0.9689 for PS-PAP sheet and R2 = 0.9598 for LS-PAP sheet). Moreover, the experimental values of the dependent variables closely matched the predicted values, indicating the reliability of the generated models. It was evident that both steaming temperature and rotation speed significantly influenced DPPH, FRAP, and SDF contents and the optimized conditions could be employed for the production of functional crispy mushroom sheets. In conclusion, the study’s novelty lies in the optimization of PAP drum drying parameters for the production of functional crispy mushroom sheets. The research creates opportunities for sustainable and nutritious products, and future perspectives could include sensory evaluation, nutritional analysis, shelf-life studies, market potential and environmental impact assessment. Overall, this research contributes to the development of healthier and eco-friendly food options.